2021
DOI: 10.1186/s12929-021-00711-z
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-mediated lysophosphatidylcholine generation promotes colitis in intestinal epithelium-specific Fut2 deficiency

Abstract: Background and aims Previous study disclosed Fucosyltransferase 2 (Fut2) gene as a IBD risk locus. This study aimed to explore the mechanism of Fut2 in IBD susceptibility and to propose a new strategy for the treatment of IBD. Methods Intestinal epithelium-specific Fut2 knockout (Fut2△IEC) mice was used. Colitis was induced by dextran sulfate sodium (DSS). The composition and diversity of gut microbiota were assessed via 16S rRNA analysis and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 37 publications
(42 reference statements)
2
50
0
Order By: Relevance
“…As a result of PC hydrolysis, LPC and fatty acids such as arachidonic acid are formed [ 126 ]. Although LPC may be toxic to the intestinal mucosa, the data on the role of arachidonic acid in IBD is more complex [ 127 , 128 ]. Although it was reported to have an ameliorating effect on the intestine [ 129 , 130 ], it was also shown to activate inflammatory pathways, which may contribute to the enhancement of colitis [ 131 , 132 ].…”
Section: Major Iecs’ Phospholipids Their Metabolism the Role In Ibd And Therapeutic Potentialmentioning
confidence: 99%
“…As a result of PC hydrolysis, LPC and fatty acids such as arachidonic acid are formed [ 126 ]. Although LPC may be toxic to the intestinal mucosa, the data on the role of arachidonic acid in IBD is more complex [ 127 , 128 ]. Although it was reported to have an ameliorating effect on the intestine [ 129 , 130 ], it was also shown to activate inflammatory pathways, which may contribute to the enhancement of colitis [ 131 , 132 ].…”
Section: Major Iecs’ Phospholipids Their Metabolism the Role In Ibd And Therapeutic Potentialmentioning
confidence: 99%
“…Braun and colleagues have shown this susceptibly is linked to altered microbiota composition and energy metabolism, and increased inflammatory tone of the colon, although mechanisms are unclear. 86 This may be linked to increased lysophosphatidylcholine production by microbes belonging the genera Escherichia, Bilophila, Enterorhabdus , and Gordonibacter in the absence of gut epithelial Fut2, which enhanced proinflammatory cytokine production and susceptibility to DSS colitis 87 ( Figure 3A ). Sonnenburg and colleagues have shown the influence of fucosylation is dependent on diet, as the microbiota changes induced by fucose deficiency were only apparent in agricultural vs. fiber-free diets.…”
Section: O-glycans In Relation To Muc2-dependent Tolerance-mediated D...mentioning
confidence: 99%
“…A recent study showed that patients with ulcerative colitis and Crohn’s disease had decreased FUT2 expression and α1,2-fucosylation in the colon[ 41 ]. In addition, Fut2 deficiency in the intestinal epithelium exacerbated colitis in epithelium-specific Fut2 knockout ( Fut2 △IEC ) mice, promoted the release of proinflammatory cytokines, and aggravated epithelial barrier damage[ 41 ].…”
Section: To the Editormentioning
confidence: 99%
“…A recent study showed that patients with ulcerative colitis and Crohn’s disease had decreased FUT2 expression and α1,2-fucosylation in the colon[ 41 ]. In addition, Fut2 deficiency in the intestinal epithelium exacerbated colitis in epithelium-specific Fut2 knockout ( Fut2 △IEC ) mice, promoted the release of proinflammatory cytokines, and aggravated epithelial barrier damage[ 41 ]. The authors demonstrated for the first time that epithelium-specific Fut2 deficiency increased susceptibility to IBD through modulation of the gut microbiome and microbiota-mediated lysophosphatidylcholine generation.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation